Robustness of Disruption Tolerant Network against Flood Attacks (International Journal of Engineering and Computer Science, 2014)
Disruption Tolerant Networks (DTNs) utilize the quality of nodes and also the opportunist contacts among node for information communications. Because of the limitation in network resources such as contact opportunity and buffer space, DTNs are at risk to flood attacks within which attackers send as several packets or packet replicas as possible to the network,so as to exhaust or overuse the restricted network resources. In this paper, there is a rate limiting to defend against flood attacks in DTNs, such that every node has a limit over the amount of packets that it will generate in every time interval and a limit over the amount of replicas that it will generate for every packet. There is a distributed scheme to discover if a node has violated its rate limits. To handle the challenge that it is troublesome to count all the packets or replicas sent by a node due to lack of communication infrastructure,the detection scheme adopts claim-carry-and check: every node itself counts the amount of packets or replicas that it has sent and claims the count to alternative nodes; the receiving nodes carry the claims once they move, and ensure if their carried claims are inconsistent once they contact; The claim structure uses the pigeonhole principle to ensure that an attacker will build inconsistent claims which can cause detection. There is a rigorous analysis on the possibility of detection, and valuate the effectiveness and efficiency of our scheme with in depth trace driven simulations.